Targeted, programmable, and precise tandem duplication in the mammalian genome - Jiao, Yaoge; Li, Min; He, Xingyu; Wang, Yanhong; Song, Junwei; Hu, Yun; Li, Li; Zhou, Lifang; Jiang, Lurong; Qu, Junyan; Xie, Lifang; Chen, Qiang; et al. (Genome Research, 2023)
Tandem duplications are frequent structural variations of the genome and play important roles in genetic disease and cancer. However, interpreting the phenotypic consequences of tandem duplications remains challenging, in part owing to the lack of genetic tools to model such variations. Here, we developed a strategy, tandem duplication via prime editing (TD-PE), to create targeted, programmable, and precise tandem duplication in the mammalian genome. In this strategy, we design a pair of in trans prime editing guide RNAs (pegRNAs) for each targeted tandem duplication, which encode the same edits but prime the single-stranded DNA (ssDNA) extension in opposite directions. The reverse transcriptase (RT) template of each extension is designed homologous to the target region of the other single guide RNA (sgRNA) to promote the reannealing of the edited DNA strands and the duplication of the fragment in between. We showed that TD-PE produced robust and precise in situ tandem duplications of genomic fragments ranging from ∼50 bp to ∼10 kb, with a maximal efficiency up to 28.33%. By fine-tuning the pegRNAs, we achieved simultaneous targeted duplication and fragment insertion. Finally, we successfully produced multiple disease-relevant tandem duplications, showing the general utility of TD-PE in genetic research.